DIGITALISASI PENGAJIAN KITAB KUNING DI PONDOK PESANTREN AS-SA’IDIYYAH 2 BAHRUL ULUM TAMBAK BERAS JOMBANG - Nurul Istiqomah; Wardatun Nadhiroh; Siti Zulaichah; Sheila Kusuma Wardani Amnesti (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
Within the pesantren tradition, kitab kuning serves as a foundational and authoritative reference for Islamic scholarship. This study focuses on the regular recitation of kitab kuning texts—Tafsīr al-Munīr by Imam al-Nawawī and Iḥyā’ ʿUlūm al-Dīn by Imam al-Ghazālī, as conducted by K.H. Ahmad Hasan, the head of Pesantren As-Sa‘īdiyyah 2 Bahrul Ulum Tambak Beras, Jombang. Employing a field-based, qualitative research approach, this study applies the lens of digital da'wah to examine how traditional pedagogical practices are being transformed through modern technology. This study's findings indicate that since 2014, the pesantren has initiated the digital broadcasting of kitab kuning recitations via YouTube. Despite limitations in audiovisual quality, which often affect sound clarity, the integration of digital media has substantially widened the reach and accessibility of these religious teachings. This transformation yields three significant impacts: (1) spatial boundaries are reduced through the enabling power of information technology; (2) audience participation is no longer limited by physical space; and (3) the availability of recitation content transcends time, allowing asynchronous access for learners. These developments mark an important step toward preserving classical Islamic scholarship while adapting to contemporary modes of knowledge transmission.